ANALISIS TINGKAT KUALITAS PELAYANAN BPJS DI PULAU KIJANG KECAMATAN RETEH - Lilik Istikhairyah; Wiwik Suryandartiwi (LPPM Universitas Awal Bros, 2022)
The Social Security Administratiion is a legal entity to administer social security programs to ensure that all people can meet the basic needs of a decent life. The suitability of the fulfillment of expectations and reality for the health services of the Social Security Administering Body is a manifestation of the satisfaction of BPJS participants. This study was conducted with the aim of analyzing the quality of BPJS Health services on Kijang Island, Reteh District. The method used in this research is the IPA (Importance Performance Analysis) method. This research is a descriptive survey research with a quantitative approach. This research was conducted from January to February 2022 at Kijang Island, Reteh sub-district, Indragiri Hilir. Around Jl. Pasar bom and Jl. Indragiri. From the measurement results of the questionnaire assessment, using the IPA (Importance Performance Analysis) analysis method, the dimensions that are in accordance with patient expectations are empathy, assurance, appearance (tangibles) and reliability (reliability). And there are no dimensions that are not in accordance with community expectations. If you look in more detail by looking at the attributes, only 40% of the attributes or 4 out of 10 of the overall attributes that need to be maintained to maintain the quality of BPJS Health Services on Kijang Island, Reteh District. From the Cartesian diagram test, there are no attributes that are in quadrant I. In quadrant II there are 4 attributes, so these four attributes need to be maintained because the service quality attributes is in fact in accordance with community expectations.